Antimicrobial Susceptibility Pattern of Community Isolates of Urinary Tract Infection in Bangladesh - Ferdous, Saieda; Islam, K M Shahidul; Barai, Lovely; Mitu, Md Zabed Ahmed; Rahman, Tania; Uddin, Md Jamal (Central Medical College Journal, 2024)
Background: Overuses and injudicious uses of maximum antibiotics that have been prescribed empirically in community acquired UTI are being the prime cause of increasing resistance pattern among uropathogens in Bangladesh. There are minimum reports on antimicrobial resistance pattern among uropathogens in different regions of Bangladesh. No reports have been carried out to determine the response of uropathogens to fosfomycin yet in our country. So, the study aimed to determine the prevalence of uropathogens causing UTI in community and to determine the increasing resistance pattern among them with special emphasis on their ciprofloxacin and fosfomycin resistance status. Methodology: Identification of isolated bacteria was performed from collected 187 culture positive cases. Their antimicrobial resistance pattern was determined by Kriby- Bauer modified disc diffusion test. Minimum inhibitory concentration test of ciprofloxacin was performed among the ciprofloxacin resistant bacteria by agar dilution method. Result: The study demonstrated a higher prevalence of UTI in female (70.1%) than in male (29.9%). The most common isolated bacteria was E. coli (80.2%) followed by Klebsiellaspp. Higher resistance rate of 171 Enterobacteriaceae to ampicillin and 3rd generation cephalosporins was observed 71.9% and 49.1%-59.7% respectively in all 6 districts of Bangladesh. Ciprofloxacin resistance has been found higher 43.9% and 50%among Enterobacteriaceae and Staphylococcus spp. More than 50% of ciprofloxacin resistant bacteria had MIC 64ug/ml. All the strains of Enterobacteriaceae were sensitive to fosfomycin except 20% Klebsiella. Conclusion: Rising antimicrobial resistance pattern among uropathogens in different districts provide physicians an important information to make a discreet choice of antibiotics in empiric therapy of community acquired UTI in Bangladesh to reduce further evolution of multidrug resistant organisms. Central Medical College Journal Vol 8 No 1 January 2024 Page: 38-46